Fungsi Kesenian Tauh dalam Kegiatan Pesta Padi pada Masyarakat Desa Lempur Tengah Kabupaten Kerinci - Reza Silfi Rizki Ayu; Marzam Marzam; Tulus Handra Kadir (SENDRATASIK UNP, 2014)
Abstract Tauh is one of  traditional art in the form of musical essembly because it has three main elements: musical instruments, singers,and dancers. Tauh is originated from Lempur Tengah, Kerinci District which is usually perfomed in harvesting party. This study was aimed at finding and describing the function and use of Tauh in harvesting party of Lempur Tengah people. The method of this study was qualitative one. The data were collected through: 1) library study, 2) observation, 3) interview, 4)documentation. The data analysis wa classified based on the focus of the study after being separated and arranged systematically. The result showed that Tauh was previously used by the king as part of harvesting rituals, and to welcome the king’s guests. This traditional art was still practiced by Lempur Tengah people until now in their harvesting party. It was used as the sign of success of the party. Along with it develoment, Tauh was also used in welcoming important guests, participatingin festival, or as the represetativeof traditional art from Kerinci in any events in province level. Therefore, Tauh has several functions for Lempur Tengah people: (1) emotional reaction function, (2) entertainment function, (3) communication function, (4) physical reaction function, (5) social integrity function, (6) social institution legalization function. Key word: Function, Tauh, Lempur Tengah, Kerinci District.